2018
DOI: 10.1590/0103-8478cr20180250
|View full text |Cite
|
Sign up to set email alerts
|

Gallus gallus domesticus: immune system and its potential for generationof immunobiologics

Abstract: Gallus gallus domesticus’ immune system is a promising tool for generation of antibody-based immunobiologics. Immunoglobulin y (IgY) is extracted from egg yolk and has equivalent functions to mammal’s igg antibody. Avian immune system can be stimulated to produce a high-quality antibody repertoire. In this review, we present an overview of avian immune system emphasizing igy and its applications as an immunobiologic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
0
9
0
1
Order By: Relevance
“…The WD method produces the greatest yield (96%) using a salt precipitation cryo-ethanol treatment, followed by the release of the IgY powder by heating, thereby stabilizing the antibody molecules ( 16 ). Hen egg yolk regularly has 8–20 mg/ml of IgY ( 11 ). Absorbance at 280 nm wavelength using NanoDrop One apparatus and Pierce TM Chicken IgY Purification Kit (Thermo Fisher Scientific TM , New York, NY, USA) were used to determine the IgY concentration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WD method produces the greatest yield (96%) using a salt precipitation cryo-ethanol treatment, followed by the release of the IgY powder by heating, thereby stabilizing the antibody molecules ( 16 ). Hen egg yolk regularly has 8–20 mg/ml of IgY ( 11 ). Absorbance at 280 nm wavelength using NanoDrop One apparatus and Pierce TM Chicken IgY Purification Kit (Thermo Fisher Scientific TM , New York, NY, USA) were used to determine the IgY concentration.…”
Section: Methodsmentioning
confidence: 99%
“…On the day 7 after hatching, the IgY is reduced as soon as the bird starts developing antibodies ( 10 ). Hen egg yolk has 8–20 mg/ml of IgY ( 11 ). Recently, we have revealed that broilers fed a novel combination of IgY and probiotics improved their behavioral activities and immunity responses ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…En base a este principio inmunológico y considerando que la yema de huevo es una fuente económica y accesible para obtener anticuerpos, la tecnología IgY desarrolla una metodología práctica, repetible, segura y de bajo costo para la producción de IgY 30 . Se comienza por inmunizar a las gallinas (por vía subcutánea, intramuscular o intradérmica), con el fin de desarrollar una respuesta inmunológica adaptativa humoral 40 . Para ello se pueden utilizar diferentes tipos de antígenos como patógenos inactivados, proteínas recombinantes o proteínas obtenidas de ADN plasmídico 41 .…”
Section: Opsonizaciónunclassified
“…One of the main features of peripheral organs of the immune system is their location. They are always localized in areas of possible penetration of antigens into an animal's organism (Nasrin et al, 2012;Doneley, 2016;Junior et al, 2018;Nochi, et al, 2018). It is well known, that most antigens penetrate into an animal's body through the digestive system.…”
Section: Introductionmentioning
confidence: 99%